The Healing Power of Forgiveness: How Failure Severity Moderates the Effect of Emotions on Forgiveness and Behavioural Intentions - Engin Tengilimoğlu (Journal of Tourismology)
Despite the undesirable consequences of service failures, it is not possible to prevent them entirely due to the characteristics of the hospitality industry. In this regard, related studies have focused on the transformation of the negative consequences of service failures into positive outcomes. In such negative situations, customer forgiveness, as a healing power, is crucial in terms of both reducing negative attitudes and behaviours and developing positive ones. This study examines the effect of post-recovery emotional responses on forgiveness and the effect of forgiveness on repurchase and positive word-of-mouth intentions, with a particular focus on the moderating role of failure severity. The study used a semi-experimental research design through the scenario technique, presenting participants with realistic fictional service failure scenarios. A 2x2 between-participants factorial design was implemented, varying the service failure severity (low vs. high) and recovery type (apology vs. discount). Data were collected from 396 participants, with 99 responses for each scenario. To address the research objectives, a multi-group structural equation model was employed. The findings indicated that positive and negative emotional response influence forgiveness, which in turn has a positive effect on repurchase and positive word-of-mouth intentions. Additionally, the effect of negative emotions on forgiveness is stronger in cases of high-severity failures, whereas positive emotions are more influential in low-severity failures. Finally, it was determined that forgiveness has a greater effect on repurchase and positive word-of-mouth in cases of low-severity failures.